Methodological basis of innovative project-oriented organizations’ management - Piterska, Varvara; Kramskiy, Sergiy (КНУБА, 2017)
One of the important factors of the spread of any innovation is its interaction with relevant socio-economic environment, which is an essential element of competing technologies. As for the innovative project is a project that includes technical, economic, legal and organizational ultimate justification of innovative activity. The result of an innovative project is the development of document includes a detailed description of product innovation, justify its viability, necessity, opportunity and attract investment forms, information on deadlines, executors and takes into account the organizational and legal aspects of its promotion. It should be noted that the success of innovative projects depends on a clear definition of goal setting of motivational activities of the project team, providing control functions on the results of the project, development of the concept of interaction of stakeholders within the project-oriented knowledge-based organization.
Keywords: innovation; project-oriented organization; methodological; project management; 005.8